Confronting Liberalisme Attack on Conventional Islam in Daun by Malim Ghozali P.K. (Malay Literature, 2024)
This study aims to analyse the liberal critiques of Islamic ideology as depicted in the novel Daun by Malim Ghozali P.K. The main issues highlighted in this article are: [i] the historical context of the development of liberalism in Malaysia as presented in both within and outside the creative work; [ii] explaining how liberal groups attempt to shape an interpretation of Islam to fit their respective agendas. This study is conducted based on a literature review that finds the attitudes of postmodernist scholars, who are evidently unsatisfied and continually deconstructing new theories that ohlm.se the true values of Islam. Therefore, this study employs the concept of New Historicism proposed by Stephen Greenblatt (1988) as an analytical framework, utilizing the concepts of constraint and mobility to view texts as constructed from sociocultural references, specifically the social values that permeate the author's identity through the societal crises the author experienced. The findings of the study indicate that Malim Ghozali P.K. strives to provide a new meaning in order to reject the liberalism ideology prevailing in society, while also critising the government's attitude at the time the novel was written, which use religious issues as a political agenda to gain support.Full text: PDF